The rise of the super-athletes, and why there is no turning back - Zok, M. (ISBS Proceedings Archive (Michigan), 2018)
Born and raised in Beirut, bio-medical engineer Mounir is the co-founder and Managing Director of N3XT Sports Inc. A world citizen who is passionate about sports, technology, entrepreneurship, and innovation, he has 15+ years` experience in various positions in the sports industry, the latest of which was Director of Technology and Innovation at the US Olympic Committee; he also sits on the working board of Women in Sports Tech. Mounir holds a PhD in Bioengineering, is fluent in four languages, and has recently moved with his wife and two children from the Silicon Valley to Barcelona. Mounir`s expertise areas of wearable technology, smart textiles and fabric, Internet of Things (IoT), artificial intelligence and cognitive computing are of interest to sports biomechanists in their goal of improving sports performance. Mounir has extensive experiences creating, managing and advising technology start ups and with the US Olympic team. Mounir`s keynote will stimulate biomechanists to think of new ways to help improve athlete`s results with technology.